Do fitness test performances predict students' attitudes and emotions toward physical education?. (2nd November 2019) - Simonton, Kelly L.; Mercier, Kevin; Garn, Alex C.
ABSTRACT: Background: The use of fitness tests in physical education (PE) receives extensive scrutiny and represents one of the most fiercely debated topics in PE research. Fitness test proponents often provide unwavering support citing their positive long-term benefits while critics underscore the corrosive long-term pitfalls associated with their use in PE. In many instances, both proponents and critics alike make these arguments with limited evidence to support their claims. Recently, critics have also highlighted the gendered nature of fitness tests, reporting that overt characteristics of these tests and their implementation create covert messages that reduce girls' motivation toward PE. Therefore, there is a clear need to gather evidence concerning the effects that fitness tests have on students' subjective experiences in PE. Purpose: The purposes of this study were twofold. First, we examine relationships between middle school students' fitness test performances and their future attitudes and emotions toward PE. Second, we investigate how these relationships vary for girls and boys. Method: A total of 273 middle school students (6th-8th grade; Male = 52%, Female = 48%) completed Fitnessgram™ battery of tests. Two weeks later, students completed two previously validated surveys about: a) their attitudes, and b) their discreet emotions (enjoyment, boredom, and anger) toward PE. First, structural equation modeling (SEM) was used to evaluate relationships for the entire sample. Once this baseline model was established, multi-group SEM identified similarities and differences in the pattern of relationships between girls and boys. Results: Findings revealed that better PACER performance predicted lower reports of future anger toward PE for both girls and boys. Conversely, increased performance on the curl-up test predicted higher rates of anger and lower rates of enjoyment toward PE. Increased PACER performance also predicted favorable attitudes for boys but not girls while increased sit-and-reach performance predicted favorable attitudes for girls but not boys. It should be noted, however, that fitness test performances explained limited amounts of variance in these outcomes, especially for girls. Conclusions: Unlike the common arguments about the valuable or harmful effects of fitness testing, our results suggested these tests had limited associations with students' future attitudes and emotions toward PE. Overall, we remain pessimistic about the use of fitness tests in PE because these PE teachers implemented fitness tests in isolation of the broader PE curriculum. Scores were neither shared with parents/guardians nor used to help students learn about their fitness. Students did not compare their results to previous tests and, to our knowledge, scores were not used for any large-scale surveillance purposes. It remains unclear how fitness test performances relate to student attitudes and emotions toward PE when implemented in a comprehensive and connected manner within the broader curriculum.